Understanding environmental management accounting (EMA) adoption: a new institutional sociology perspective - Jalaludin, Dayana; Sulaiman, Maliah; Nik Ahmad, Nik Nazli (Emerald Group Publishing Limited, 2011)
The purpose of this research paper is to report the results of a study that explains the relationship between institutional pressure and environmental management accounting (EMA) adoption. Specifically, it looks at the pressure of government and other parties in society concerning EMA adoption among manufacturing companies in Malaysia.